A two-step etching route to ultrathin carbon nanosheets for high performance electrical double layer capacitors. Issue 21 (16th May 2016) - Ding, Bing; Wang, Jie; Wang, Ya; Chang, Zhi; Pang, Gang; Dou, Hui; Zhang, Xiaogang
Abstract : A two-step etching route is proposed to prepare ultrathin carbon nanosheets, which guarantee large ion-accessible surface area and shorten ion transport length in the nanoscaled structure. Abstract : Two-dimensional (2D) carbon materials have attracted intense research interest for electrical double layer capacitors (EDLCs) due to their high aspect ratio and large surface area. Herein, we propose an exfoliation–chlorination route for preparing ultrathin carbon nanosheets by using ternary layered carbide Ti3 AlC2 as the precursor. Due to the large intersheet space of exfoliated layered carbide (MXene), the as-prepared carbon nanosheets exhibit a thickness of 3–4 nm and a large specific surface area of 1766 m 2 g −1 with hierarchical porosity. These features significantly improve the ion-accessible surface area for charge storage and shorten the ion transport length in the thin dimension. As a result, the carbon nanosheets show a high specific capacitance (220 F g −1 at 0.5 A g −1 ), remarkable high power capability (79% capacitance retention at 20 A g −1 ) when measured in a symmetrical two-electrode configuration in an aqueous electrolyte. The method described in this work provides a new route to prepare 2D electrode materials from a bulk precursor, thus exploiting their full potential for EDLCs.